PERSEPSI GURU TERHADAP PERILAKU ETIK KEPALA SEKOLAH SEBAGAI SUPERVISOR PADA SEKOLAH DASAR NEGERI DI NAGARI BALAH AIE KECAMATAN VII KOTO SUNGAI SARIK KABUPATEN PADANG PARIAMAN - Wulan Sari; Hadiyanto Hadiyanto (Jurnal Bahana Manajemen Pendidikan, 2019)
This study aims to obtain information about teacher perceptions of ethical behavior of principals as supervisors at SDN in Nagari Balah Aie, Kec. VII Koto Sungai Sarik Kab. Padang Pariaman. Ethical behavior includes the characteristics related to personality and democratic supervisors expectations of all parties. The ethical behavior of principals as supervisors is very important in getting maximum supervision results. This type of research is a descriptive study with a population of 43 people. Thus this research is called population research. The results showed that the teacher's perception of the principal's ethical behavior as a supervisor was good with a score of 4.0. Viewed from the aspect of personality related to being in the good category with a score of 4.1. Furthermore, in the aspect of a democratic supervisor the expectations of all parties are also in the good category with a score of 3.9. As for what needs to be considered again is the attitude of sympathy for the teacher by providing assistance and asking in advance the obstacles faced by the teacher in learning. Then a firm and objective (impartial) attitude by giving sanctions and a firm attitude towards negligent teachers regardless of teacher status outside the school. Next is fair and honest attitude by not distinguishing supervision services between one teacher and another, and providing guidance in accordance with the needs of each teacher. Whereas in the sub-indicators know how to delegate tasks and responsibilities can be done by involving and entrusting the teacher in the successful implementation of supervision. Then by suggesting the teacher to share teaching experiences and always discuss the methods, sources and learning media